2016
DOI: 10.1177/0969733016658793
|View full text |Cite
|
Sign up to set email alerts
|

Test of a Dignity Model in patients with heart failure

Abstract: According to the results, the necessity of using appropriate tools to assess various aspects of patients' dignity by clinical healthcare staff and design activities with particular focus on the main factors affecting dignity such as illness related worries and social dignity is recommended. Attention to this issue in everyday clinical practice can facilitate health professionals/nurses to potentially improve their patients' dignity, develop quality of care and treatment, and improve patients' satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(42 citation statements)
references
References 45 publications
1
38
2
1
Order By: Relevance
“…For another 13 instruments, it was not possible access the full questionnaire; therefore, we could not assess the single items used within the questionnaires, and hence, the elements of psychosocial fundamentals of care under investigation were not clear to the reader (Caring Behaviors Inventory (CBI): Aupia, Lee, Liu, Wu, & Mills, 2018; He et al, 2013; Papastavrou et al, 2012a; Papastavrou et al, 2012b; Patient Needs Assessment in Palliative Care (PNAP): Buzgova, Kozakova, Sikorova, Zelenikova, & Jarosova, 2016; questionnaire used by Comiskey et al, 2014; questionnaire used by Ehrlander, Ali, & Chretien, 2009; Revised Humane Caring Scale (RHCS): Goh, Ang, Chan, He, & Vehviläinen‐Julkunen, 2016; questionnaire used by Göransson & Von Rosen, 2010; questionnaire used by Raee, Abedi, & Shahriari, 2017; Consumer Quality index (CQ‐index): Teunissen, Rotink, & Lagro‐Janssen, 2016; and questionnaire used by Yousuf, Fauzi, How, Akter, & Shah, 2009). This is despite in some cases a clear statement that the element of psychosocial fundamentals of care being investigated was witnessed by a clear statement in the title of the tool (Inherent Dignity Questionnaire (IDQ), Social Dignity Questionnaire (SDQ) and Dignity Conserving Repertoire Questionnaire (DCRQ): Bagheri, Yaghmaei, Ashktorab, & Zayeri, 2018a; Bagheri, Yaghmaei, Ashktorab, & Zayeri, 2018b). However, there was limited evidence of these specific measurements being reported within the paper.…”
Section: Resultsmentioning
confidence: 99%
“…For another 13 instruments, it was not possible access the full questionnaire; therefore, we could not assess the single items used within the questionnaires, and hence, the elements of psychosocial fundamentals of care under investigation were not clear to the reader (Caring Behaviors Inventory (CBI): Aupia, Lee, Liu, Wu, & Mills, 2018; He et al, 2013; Papastavrou et al, 2012a; Papastavrou et al, 2012b; Patient Needs Assessment in Palliative Care (PNAP): Buzgova, Kozakova, Sikorova, Zelenikova, & Jarosova, 2016; questionnaire used by Comiskey et al, 2014; questionnaire used by Ehrlander, Ali, & Chretien, 2009; Revised Humane Caring Scale (RHCS): Goh, Ang, Chan, He, & Vehviläinen‐Julkunen, 2016; questionnaire used by Göransson & Von Rosen, 2010; questionnaire used by Raee, Abedi, & Shahriari, 2017; Consumer Quality index (CQ‐index): Teunissen, Rotink, & Lagro‐Janssen, 2016; and questionnaire used by Yousuf, Fauzi, How, Akter, & Shah, 2009). This is despite in some cases a clear statement that the element of psychosocial fundamentals of care being investigated was witnessed by a clear statement in the title of the tool (Inherent Dignity Questionnaire (IDQ), Social Dignity Questionnaire (SDQ) and Dignity Conserving Repertoire Questionnaire (DCRQ): Bagheri, Yaghmaei, Ashktorab, & Zayeri, 2018a; Bagheri, Yaghmaei, Ashktorab, & Zayeri, 2018b). However, there was limited evidence of these specific measurements being reported within the paper.…”
Section: Resultsmentioning
confidence: 99%
“…It was indicated that, the dignity of the hospitalized patients can be threatened by some certain factors, including patients' inability to play important parts in life, lack of support from friends and the medical personnel, and uncertainty about the future [11]. In a study by Bagheri et al (2018), disregarding patient participation and failure to support patients were reported to cause patients' loss of dignity [59]. Sideli et al (2010) reported that people who get less social support are more likely to endure higher levels of stress and pain [27].…”
Section: Discussionmentioning
confidence: 99%
“…Questions from the nursing staff that probed into the patient's personal life such as how the illness had impacted intimacy was regarded to be unethical, rude, and infringing on patient's privacy (38). Recurrent interactions with health care providers and hospitalisations increased patient vulnerability and the risk of losing personal and physical privacy that threatened dignity (42)(43)(44). This could be related to the imperfect health care system and increased vulnerability of the patients.…”
Section: Themesmentioning
confidence: 99%
“…Abundance of resources: Economic burdens and overshadowing fears of not getting hold of the essential medical resources and health services due to unavailability or inaccessibility are damaging to personal identity and dignity (38,43,44,49). Recurrent admissions to the hospital are associated with high expenses, nancial burdens, increased reliance on family support, and heightened patient vulnerability (42)(43)(44). In contrast, economic prosperity is related to perceptions of being worthwhile, digni ed, having a purposeful life, and a meaningful social role (49).…”
Section: Themesmentioning
confidence: 99%